Peluang dan Tantangan Becak Wisata dalam Mendukung Pariwisata di Kabupaten Jember - Kamal, Mushthofa; Dewangga, Vigo (Jurnal Master Pariwisata (JUMPA); Volume 08, Nomor 02, Januari 2022, 2022)
The aim of this research is to identify opportunities and challenges for a tourist pedicab in supporting Jember Regency tourism. The method used in this research is descriptive with qualitative data. The data collection technique used snowball sampling and accidental sampling. The results of this study indicate that the existence of a tourist pedicab has opportunity to support the tourism in Jember Regency, such as: 1) as a mode of transportation. 2) as a tour guide. 3) as a middleman to various restaurants. 4) as a middleman to various inns. 5) as a middleman to various souvenir places. 6) as a middleman to a tourist attraction. But on the other hand, the tourist pedicab also has several challenges, such as: 1) uneven road conditions. 2) a one-way street. 3) the existence of online-based transportation. 4) there is no famous tourist attraction in urban areas. 5) not yet skilled tourist pedicab drivers in serving tourists. Collaboration with various partners is needed to support tourism in Jember Regency through a tourist pedicab. Keywords: Tourism, Tourist Pedicab, Urban Tourism.